Strategic Innovation in Green Accounting: Integrating Social Responsibility and Business Performance in Indonesian Corporations - Risqi Amalia; Norlin Terontja; Nina Yusnita Yamin; Rahayu Indriasari; Andi Chairil Furqan (Yayasan Cerdas Pedia Indonesia, 2025)
Green accounting represents a strategic innovation that fundamentally integrates environmental sustainability with organizational performance in Indonesian corporations. This research evaluates the implementation of green accounting methodologies, including Material Flow Cost Accounting (MFCA) and Life Cycle Assessment (LCA), demonstrating that these practices extend beyond regulatory compliance to constitute competitive advantages through enhanced resource efficiency and operational cost reduction. The study employs a mixed-methods approach integrating quantitative econometric modeling with qualitative case analysis of companies listed on the Indonesian Stock Exchange (BEI) between 2018–2024, examining relationships between green accounting implementation, financial performance metrics including Return on Assets (ROA), firm valuation, and environmental performance. Key findings indicate that green accounting adoption, when operationalized through advanced methodologies and supported by digital technologies including Internet of Things (IoT), Artificial Intelligence (AI), and blockchain systems, significantly strengthens corporate environmental accountability, enhances stakeholder legitimacy, and attracts ESG-sensitive capital inflows. The research contextualizes green accounting within Indonesia's macroeconomic framework as an instrumental policy mechanism for achieving Sustainable Development Goals through internalization of previously externalized environmental costs and facilitation of inclusive growth mechanisms, particularly green employment creation and poverty reduction in vulnerable communities. The harmonization of Indonesia's Sustainability Disclosure Standards (SPK) roadmap with the International Sustainability Standards Board (ISSB) framework establishes a coherent regulatory environment enhancing national economic competitiveness. However, realizing these benefits requires comprehensive capacity-building initiatives targeting Micro, Small, and Medium Enterprises (MSMEs) and sustained policy commitment to bridge implementation maturity gaps, positioning Indonesia as a sustainable accounting innovation leader within Southeast Asia's developing economies.